IMPACT BEHAVIOR ANALYSIS OF HOLLOW EXTRUDED PROFILES BASED ON GISSMO - WANG Lihong; LÜ Lin (Jixie qiangdu)
To study the response characteristics of the hollow extruded profile of the vehicle after the collision, the generalized incremental stress state-damage model (GISSMO) was introduced and the finite element simulation was carried out. Firstly, based on the test results of 6082-T6 aluminum alloy, the dynamic and static mechanical properties and fracture behavior under different stress states were characterized by the modified Johnson-Cook (MJC) model and DF2016 model respectively. Secondly, the parameter calibration of GISSMO was carried out based on the combination of LS-OPT soft ware and manual optimization. Then, according to the mesh size effect, the mesh size dependence correction was carried out, and the effectiveness of the model and correction were verified by comparison between the experiment and simulation. Finally, the impact simulation analysis of a hollow extruded profile on the side wall of a vehicle body was carried out, and the impact of material damage and fracture on the simulation results was compared. The results show that GISSMO can more accurately reflect the response of profiles under longitudinal impact than without considering the damage and fracture of materials.